WOMEN REPRESENTATIONS AND TECHNOCULTURAL PATRIARCHY IN CAM, CAUGHT IN THE WEB, AND FIFTEEN MILLION MERITS - Ledesma, Jan Raen Carlo Mijaro; Manalastas, Aldrin Enciso (International Journal of Humanity Studies (IJHS), 2025)
This paper examined women protagonists from three media samples: Cam (2018), Caught in the Web: The Murders Behind Zona Divas (2024), and Black Mirror’s Fifteen Million Merits (2011). It analyzed women as the subjects of visual pleasure and extended the discourse on gender and technology, shedding light on how technology is grounded in the project of patriarchy. Capitalizing on the critical research design and on the feminist film theory of Laura Mulvey, and feminist and technology theories of Judy Wajcman, Joan Pujol and Maria Montenegro, the analysis demonstrated how the samples partook in the dynamic correlations of visual pleasure, feminism and technology with them exploring the political specificities of sexual hierarchies and their emplacements in a technological capitalistic world, the patriarchal shaping of technology espousing the exclusion and reification of women, the compartmentalization of their bodies and autonomies by technology leading to their pessimistic and subjugated portrayals unveiling the image of men as the forerunners of technological control. The feminist issues that they faced opened the subject of technology as a gendered culture and entity seriously shaped by phallocentric ideologies, conveying how the ideologies of maleness and androcentrism can steer its complexities.